THE IMPACT OF PRICE, PRODUCT QUALITY, AND ELECTRONIC WORD OF MOUTH ON PURCHASE DECISIONS FOR BENING’S KINCARE PRODUCTS IN KARAWANG - Sari, Yuniar; Jajang, Dede; Hersona, Sonny (At-Tadbir : jurnal ilmiah manajemen, 2024)
The objective of this study is to ascertain the impact of price, product quality, and electronic word of mouth on the purchasing decisions regarding Bening's skincare products in Karawang. Employing quantitative research with hypothesis testing, the research involved a sample of 105 consumers of Bening's Skincare products in Karawang.The analytical methods applied include multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t-test, F-test, and classical assumption tests using SPSS version 20 statistical software. Primary data for the study were obtained through a questionnaire. The findings of this research affirm that the price significantly influences the purchasing decisions for Bening's Skincare products in Karawang. Moreover, product quality plays a significant role in influencing the decision to purchase Bening's skincare products in Karawang. However, electronic word of mouth does not exhibit a significant impact on purchasing decisions for Bening's skincare products in Karawang. Additionally, the combined influence of price, product quality, and electronic word of mouth simultaneously affects the purchasing decisions for Bening's Skincare products in Karawang.